Determinants of Occupational and Residential Functioning in Bipolar Disorder - Depp, Colin A (2011)
BACKGROUND: Bipolar disorder is associated with reduced rates of employment and residential independence. The influence of cognitive impairment and affective symptoms on these functional attainments has received little previous attention and is the focus of this study. METHOD: A total of 229 adult outpatients with bipolar disorder without active substance use disorders and with an average of mild severity of affective symptoms were included in the analyses. After adjusting for sociodemographic and illness history covariates, univariate and multivariate analyses were used to evaluate the independent and interactive associations of neurocognitive ability, performance-based functional capacity, and affective symptom severity with residential independence, occupational status and number of hours worked. RESULTS: A total of 30% of the sample was unemployed and 18% were not independently residing. Neurocognitive ability was the strongest predictor of any employment, but depressive symptom severity was the only variable significantly related to hours worked. The strongest predictor of residential independence was performance-based functional capacity. Affective symptoms and neurocognitive ability were independent (non-interactive) predictors of occupational and residential status. LIMITATIONS: This is a cross-sectional study and thus causal direction among variables is unknown. The sample was ethnically homogeneous and thus the results may not generalize to ethnically diverse samples. CONCLUSIONS: This study confirmed elevated rates of unemployment and residential non-independence in adults with bipolar disorder. Interventions targeting cognitive deficits and functional capacity may increase the likelihood of any employment or residential independence, respectively. Interventions targeting depressive symptoms may be most influential on work outcomes among those already employed.